Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1097/aln.0b013e3181d3d624
|View full text |Cite
|
Sign up to set email alerts
|

Role of Caveolin-3 and Glucose Transporter-4 in Isoflurane-induced Delayed Cardiac Protection

Abstract: Background Caveolae are small, flask-like invaginations of the plasma membrane. Caveolins are structural proteins found in caveolae that have scaffolding properties to allow organization of signaling. We tested the hypothesis that delayed cardiac protection induced by volatile anesthetics is caveolae/caveolin-dependent. Methods An in vivo mouse model of ischemia-reperfusion injury with delayed anesthetic preconditioning was tested in wild-type, caveolin-1 knockout, and caveolin-3 knockout mice. Mice were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 56 publications
2
59
0
Order By: Relevance
“…The declining I/R tolerance is not unexpected given the influences of caveolae and cholesterol on key determinants of stress resistance (8,18,31,32,44,(52)(53)(54)(55)(56)(57). For example, M␤CD consistently inhibits BK Ca channel function across different cell types, and the channel has been implicated in cytoprotection and I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The declining I/R tolerance is not unexpected given the influences of caveolae and cholesterol on key determinants of stress resistance (8,18,31,32,44,(52)(53)(54)(55)(56)(57). For example, M␤CD consistently inhibits BK Ca channel function across different cell types, and the channel has been implicated in cytoprotection and I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these observations support the growing body of data that led to the recognition of myocardial lipid rafts and their associated proteins as modulators of cardiac performance and as novel therapeutic targets [73][74][75].…”
Section: Molecular Basis Of Dilated Cardiomyopathy: Past and New Actorsmentioning
confidence: 53%
“…CON control group, SEVO sevoflurane group. *Significantly (p \ 0.05) different from CON group after reperfusion, n = 4 per group mechanisms have been extensively studied such as K ATP channel, NF-jB, 12-lipoxygenase and so on [5][6][7], but very few studies have focused on the role of apoptosis in delayed APC. Studies demonstrated that APC with sevoflurane protects myocardium from I/R not only protects myocardial by reduced infarct size, but also improves cardiac functional recovery, decreases post-ischemic myocardial stunning and attenuates myocardial apoptosis [3,8,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Kehl et al [13] reported that, unlike ischemic preconditioning, isoflurane does not produce a second window of protection (SWOP) 24 h after administration in dogs. However, others have reported that isoflurane has delayed cardiac protective effects using in vivo mouse myocardial I/R model [6] and delayed APC with sevoflurane has a similar effect on myocardial protection [2][3][4].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation